Penyelesaian Kontrak Konstruksi Dalam Hal Terjadi Keterlambatan Pengadaan Tanah Untuk Kepentingan Umum - Arfando, Mohamad Sondan; Azheri, Busyra; Hasbi, Muhammad (Nagari Law Review, 2024)
As a follow-up to the Decree of the Governor of DKI Jakarta Province Number 2779 of 2015 concerning Determination of Locations for the Construction of the Ciliwung River Sudetan Inlet Towards the East Flood Canal in Bidara Cina Subdistrict, the East Jakarta Land Office together with Ciliwung Cisadane River Basin Organization from Ministry of Public Works and Housing carried out the Inventory and Identification implementation stages for land acquisition for the inlet location. In its implementation, there were problems in RW.04 Bidara Cina Subdistrict, namely a land dispute between residents affected by the project and the legal land owners. The affected residents challenged the Governor's location determination to the PTUN with decision no. 59/G/2016/PTUN-JKT on March 15 2016. This hampered the land acquisition process and had an impact on the implementation time of the Sudetan development. This research aims to describe and analyze how land acquisition is carried out in the construction of the Ciliwung River Sudetan Inlet to the East Flood Canal, what factors cause obstacles to land acquisition and what is the strategy for completing construction contracts in the event of delays in land procurement for the public interest. This research is a qualitative descriptive research with an empirical juridical approach. The results of the research were that the affected residents' lawsuit was caused by the socialization of the project carried out by the government which did not meet the residents' wishes so that an agreement on the value of adequate compensation was not reached. On the government side, delays in the land acquisition process at that time were caused by a lack of funds and the administrative process for resolving compensation payments was not yet 100% complete. There was a delay in the completion of the construction contract in terms of land acquisition for public interests for the construction of the Ciliwung River Sudetan Inlet to the East Flood Canal, which was carried out by the government in terms of dispute resolution, land acquisition and contracts.